Biomedical Applications of Metal–Organic Frameworks at the Subcellular Level. Issue 9 (9th July 2021) - Xue, Jueyi; Liu, Jian; Yong, Joel; Liang, Kang
Abstract : Organelles, or subcellular structures, are the fundamental functional units in almost all eukaryotic cells. Consequently, they play a critical role in the development of various biomedical applications, such as targeted drug delivery, biosensing, imaging, and biomimetics. Many efforts are devoted to developing nanosystems that can target specific organelles in a controlled manner. A series of nanomaterials with high porosity, stability, and easy‐to‐tailor properties, named metal–organic frameworks (MOFs), have shown to be a promising new class of nanocarriers and bioprotective exoskeletons for biomedical and biocatalytical platforms at the subcellular level. Herein, the recent state‐of‐the‐art progress of MOF nanomaterials for bioapplications at the subcellular level is highlighted. In the first section, MOF‐derived biomimetics organelles and subcellular structures are highlighted. Then, the strategies of organelle‐targeted MOF therapy and biosensing are illustrated. Next, MOF‐based biopreservation of organelles is introduced. Finally, a personal perspective about the challenges and future innovative designs is discussed. Abstract : This review highlights the state‐of‐the‐art progress of metal–organic framework (MOF) nanomaterials for bioapplications at the subcellular level, including MOF‐based organelle mimics, organelle‐targeted drug delivery and biosensing, and biopreservation of organelles.